Body composition assessment in quadriplegic athletes (Revista horizonte, 2015)
The aim of this study was to evaluate the body composition in athletes with spinal cord injury. Double indirect anthropometric measures were used. The sample was comprised of eight male athletes with spinal cord injury (age, 21 to 35 y). We calculated body mass index (BMI), body size of the framework (TAC) and sum of skinfolds (Σ9DC). We used descriptive statistics (software SPSS® 11.0). The average value of the group on the Σ9DC was 144.9±55.42. With respect to BMI, the average was 20.02±3.07 and that 65.5% of the individuals are within the ideal standards while 37.5% are below the ideal standard, and finally, the TAC, with an average of 1510.05±101.05. It was observed that anthropometric assessments, demonstrated to be effective for analyzing the aspects of quality of life, but the training, there are limitations.